2018
DOI: 10.1002/ejp.1185
|View full text |Cite
|
Sign up to set email alerts
|

Medical cannabis: A forward vision for the clinician

Abstract: Legalization of medical cannabis has bypassed usual drug regulatory procedures in jurisdictions worldwide. Pending sound evidence for effect in many conditions, physicians must continue to provide competent empathetic care with attention to harm reduction. A vision to navigate the current challenges of medical cannabis is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
0
27
0
1
Order By: Relevance
“…Many clinicians remain skeptical of cannabis as a viable treatment option, either due to the stigma surrounding cannabis use or the belief that there is not enough clinical evidence for them to feel confident providing patients with cannabis recommendations. 169 This is unsurprising, given that 85% of recent medical school graduates still receive no education whatsoever about cannabis throughout their training, residencies, or fellowships. 170 As the evidence in this field accumulates, it will be critically important to widen opportunities for clinicians to participate in Continuing Medical Education programs, which include the harm reduction and medical benefits that cannabis could provide.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Many clinicians remain skeptical of cannabis as a viable treatment option, either due to the stigma surrounding cannabis use or the belief that there is not enough clinical evidence for them to feel confident providing patients with cannabis recommendations. 169 This is unsurprising, given that 85% of recent medical school graduates still receive no education whatsoever about cannabis throughout their training, residencies, or fellowships. 170 As the evidence in this field accumulates, it will be critically important to widen opportunities for clinicians to participate in Continuing Medical Education programs, which include the harm reduction and medical benefits that cannabis could provide.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…A recent nationally representative study showed that the risk of cannabis use and cannabis use disorders has increased, especially in states where medical cannabis laws have been passed (Hasin et al, 2017). The use of cannabis to treat medical issues and symptomology is also increasing in the US (Hill, 2015) and globally (Fitzcharles & Eisenberg, 2018), and the rates at which people are using medical cannabis have increased in states where medical cannabis laws have been passed (Cerda, Wall, Keyes, Galea, & Hasin, 2012). In California alone, which legalized medical cannabis in 1996, there were two million individuals in 2012 that were using cannabis medically (Ryan-Ibarra, Induni, & Ewing, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…New members joining PCC, especially if cannabis-naive (which represent approximately 60%), were instructed on how to properly self-administer Trokie ® lozenges, embracing the “start low, go slow” motto proposed by clinicians for the use of herbal cannabis ( MacCallum and Russo, 2018 ), starting with 1/4th of a 50 mg CBD lozenge (12.5 mg) two or three times a day for 3 days. After this initial period, members are coached by PCC clinical personnel on how to slowly adjust their intake of THC and CBD to achieve optimal symptom relief, with follow-up calls on days 4, 7, 14, and each time they place a new order, under the guiding principle of “primum non nocere” ( Fitzcharles and Eisenberg, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many countries have passed legislation permitting the use of cannabis for medical reasons. This has given patients access to both herbal material and cannabis-based products, bypassing the strict regulatory procedures that usually apply to pharmaceutical development ( Fitzcharles and Eisenberg, 2018 ). Further, legalization of cannabis for recreational purposes in several states of the Union as well as in internationally-relevant countries, such as Canada, conferrers cannabis an intriguing dual status, both as a pharmaceutical substance and a mere commodity, thus creating a complex regulatory scenario.…”
Section: Introductionmentioning
confidence: 99%